Analysis Of Strategies To Increase Rice Paddy Productivity To Support The Land Optimization Program (OPLA) In Tanah Laut Regency - Septia Hayati Hayati; Muhammad Fauzi Makki; Yusuf Azis (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze internal and external factors of lowland rice farming and to formulate priority strategies for increasing rice productivity through the Land Optimization Program (OPLA) in Tanah Laut Regency. The main problem addressed is the suboptimal rice productivity under OPLA implementation and the disparity in performance between small-scale and large-scale farmers.  The research employed a quantitative approach supported by qualitative data. Primary data were collected through structured interviews with 60 purposively selected rice farmers participating in OPLA, while secondary data were obtained from relevant institutions. Data analysis applied a strategic management framework using the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, SWOT matrix, and the Quantitative Strategic Planning Matrix (QSPM). The results indicate that the internal condition of rice farming is moderately strong, with an IFE score of 2.78, while the external environment is relatively favorable, with an EFE score of 2.85. The combined scores position OPLA in Cell V (hold and maintain) of the Internal–External matrix. The recommended priority strategy is optimizing land utilization through enhanced adoption of cultivation technologies and strengthened support for production inputs. However, strategy formulation is differentiated by landholding typology: for small-scale farms, strengthening farmer group institutions is prioritized, whereas for large-scale farms, reinforcing collective block management—particularly in planting schedules, water governance, and harvest coordination—is emphasized. Overall, the study concludes that increasing rice productivity under OPLA requires a contextual, typology-based strategic approach to ensure program effectiveness and long-term sustainability.